ANALISIS PENYELESAIAN SENGKETA TERHADAP ANAK YANG MELAKUKAN WANPRESTASI DALAM PERJANJIAN SEWA MENYEWA ANTARA PEMILIK BANGUNAN DENGAN PT. INDOMARCO PRISMATAMA - ERLINA B (PRANATA HUKUM, 2017)
Developments in the globalization era of business world engaged in the growing trade in Indonesia. This is the occurrence of agreements between interested parties and in the field of trade. In this case in Lampung Province licensing from PT. Indomarco Prismatama to Indomaret. In life in society, especially in business world, we see there are some Building Owner who do cooperation with Indomaret as license holder of PT. Indomarco Prismatama. This basic issue encourages the author to examine the lease agreement between the owners of the building with PT. Indomarco Prismatama. The problem in this research is “How is the settlement if one of the parties makes a default in the lease agreement between the owner of the building and PT. Indomarco Prismatama?”. Based on the results of the study it can be concluded that if the Second Party neglects to not fulfill its obligation to the agreed lease period of the compensation arrangement, then the Second Party is now also on time, i.e. in the event that the Second Party neglects its obligation to vacate the Building at the time of the Agreement The Lease Rents expire, then the Second Party hereby authorizes Substitution on the First Party now and for later.